Strategies to Overcome Failures in T-Cell Immunotherapies by Targeting PI3K-δ and –γ - Chandrasekaran, Sanjay; Funk, Christopher Ronald; Kleber, Troy; Paulos, Chrystal M.; Shanmugam, Mala; Waller, Edmund K. (Frontiers in Immunology, 2021)
PI3K-δ and PI3K-γ are critical regulators of T-cell differentiation, senescence, and metabolism. PI3K-δ and PI3K-γ signaling can contribute to T-cell inhibition via intrinsic mechanisms and regulation of suppressor cell populations, including regulatory T-cells and myeloid derived suppressor cells in the tumor. We examine an exciting new role for using selective inhibitors of the PI3K δ- and γ-isoforms as modulators of T-cell phenotype and function in immunotherapy. Herein we review the current literature on the implications of PI3K-δ and -γ inhibition in T-cell biology, discuss existing challenges in adoptive T-cell therapies and checkpoint blockade inhibitors, and highlight ongoing efforts and future directions to incorporate PI3K-δ and PI3K-γ as synergistic T-cell modulators in immunotherapy.